Gaya Kepemimpinan Kepala Sekolah dalam Meningkatkan Mutu Lembaga di Madrasah Ibtidaiyah Al Ishlahiyah Wonorejo - Lana Najma Kamila; Basri Basri; Parmujianto Parmujianto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to determine the leadership style in improving the quality of institutions in Madrasah Ibtidaiyah Hidayatul Ula Probolinggo. Where leadership is the most important issue or important for an institutional body, it is because the leadership style is part of influencing the success of the organization or institutional body itself to achieve these goals. The purpose of this research is to understand the role and determine the relationship between the leadership of the madrasa head in improving the quality of the institution at Madrasah Hidayatul Ula Probolinggo. This type of research is descriptive qualitative research, which is describing or describing an ongoing problem and in collecting reports in the form of data. The data collection process includes using the method of interview, observation, documentation (data review). The conclusions of this study are that the leadership style of The principal's leadership style in improving the quality of the institution has a significant effect, namely through the process of coaching and strengthening. The quality of the institution is formed from the leadership style of the madrasah principal in the quality of learning and always conducting supervision in the learning process so that the quality of the teaching-learning process is better.